Analysis of Alternative Clean Water Supply in Bira Beach Tourism Area, Bulukumba Regency - Sumpala, Andi Gita Tenri; Rajab, Arini; Mahyuddin, Mahyuddin (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Clean water is used daily for drinking, sanitation, and other activities that support human life. Clean water has requirements in terms of quality and quantity. Clean water requirements include physical, chemical, and biological parameters with specific threshold values so that, it will not cause side effects when consumed. The quantity of clean water provided can be seen from the amount of raw water available to meet regional needs. This study aims to determine the potential for a clean water supply in the Bira Beach Tourism Area of Bulukumba. The alternatives include boreholes, Regional Drinking Water Company, rainwater harvesting, domestic wastewater reuse, and seawater desalination. The method used in this research is Break Event Point (BEP) to determine the economic price of each alternative water supply and the Analytical Hierarchy Process (AHP) method to choose the most suitable alternative to be used by calculating six criteria, namely quality, quantity, continuity, ecology, and technology. The results of this study indicate that the lowest BEP value is a borehole at IDR 302, then Regional Drinking Water Company at IDR 2,500, seawater desalination at IDR 4,022, domestic wastewater reuse at IDR 6,300 and rainwater harvesting at IDR 16,834, and the results of research using the AHP method rainwater harvesting and wastewater reuse get the highest value of 108.52 and 69.04 respectively.